Cross-Cultural Adaptation and Validation of the Attitudes Toward Suicide Questionnaire Among Healthcare personnel in Malaysia. (3rd May 2017) - Siau, Ching Sin; Wee, Lei-Hum; Ibrahim, Norhayati; Visvalingam, Uma; Wahab, Suzaily
Understanding attitudes toward suicide, especially among healthcare personnel, is an important step in both suicide prevention and treatment. We document the adaptation process and establish the validity and reliability of the Attitudes Toward Suicide (ATTS) questionnaire among 262 healthcare personnel in 2 major public hospitals in the Klang Valley, Malaysia. The findings indicate that healthcare personnel in Malaysia have unique constructs on suicide attitude, compared with the original study on a Western European sample. The adapted Malay ATTS questionnaire demonstrates adequate reliability and validity for use among healthcare personnel in Malaysia.